Coping Strategies of Working Women Examined from Personality Types - Maghfiroh, Fitrania; Fatika, Farellia Dwi (Proceedings of The International Conference on Psychology and Education, 2025)
The emergence of the COVID-19 outbreak has increased the dynamics of the dual roles attached to women. This research was conducted to find out how different coping strategies are in dealing with the COVID-19 outbreak in terms of personality types among working women. This research was conducted with the help of a Google Form through a purposive sampling technique for collecting data with a total sample of 118 women who were required to actively work outside the home. The results showed that the chi-square analysis test resulted in significant differences in coping strategies in dealing with COVID-19 in terms of personality types in working women, which had a significance value of 0.000, which meant that there were significant differences.